Estudo léxico-semântico da terminologia das enfermidades oculares na Bahia (Alagoinhas, Euclides da Cunha, Jeremoabo) - Santos , Celineide Camões dos (2022)
This study seeks to investigate the terminological variations of eye diseases; based on data collected by the Project Atlas Linguístico do Brasil (ALiB) team in Alagoinhas, Euclides da Cunha, and Jeremoabo. The corpus of this study consisted of a Semantic-Lexical Questionnaire referring to the semantic area of ​​the human body and the names corresponding to the six questions were analyzed: 091 – blind in one eye; 092 - Cross-eyed; 093 – myopic; 094 – third/widow; 095 – conjunctivitis/pain in the eyes; 096 – cataract. Our objective is to analyze the systematized data, in a comparative way between the locations of Alagoinhas, Euclides da Cunha, and Jeremoabo, taking into account the sociocultural variables: gender, age group, and location, to understand the uses of terminology concerning eye diseases. This investigation is based on the theoretical assumptions of Weinreich, Labov, and Herzog, (1968, 2006); Labov (2008 [1972]); in Third Wave Sociolinguistics (ECKERT, 2002); in addition to the studies by Cabré (1993); Biderman (1996); Krieger and Finatto, (2008); Faulstich (1995); Cardoso (1996). In addition to knowing the different terminological variants of eye diseases, our objective with this research was to verify the sociocultural variables that favor the use of linguistic variants. Thus, the results of this work seek to expand studies on the lexicon of eye diseases and disseminate data from the ALiB Project and contribute to research carried out in the field of Sociolinguistics, Dialect Socioterminology.